The Preventable Effect of Taekwondo Sport among Cadets and Junior' Bone Mineral Density: DEXA Assessment - Hadeel Ali Ghazzawi; Adam Tawfiq Amawi; Hamza Alduraidi; Malik Juweid; Hussam H. Alhawari; Mousa A. Al-Abbadi; Ali M. Alabbadi; Lana Salah Subhi AlNemer (MDPI AG, 2023)
Athletes competing in Taekwondo (TKD), the weight-category sport, tend to rapidly lose weight to achieve the desired body weight for better competitive results. Little is known about the effect of rapid weight reduction on bone mass density (BMD), especially during childhood and adolescence. The current study aimed to investigate the impact of rapid weight loss on BMD among cadets and juniors TKD athletes. A descriptive case series study design was conducted and collected from 28 males and females aged 12-17 years old, with mean age 14.4 ± 1.7. Dual-energy X-ray absorptiometry (DEXA) was used for both BMD and body composition assessment, and laboratory tests were also performed for the total calcium (Ca), TSH, free T4 (FT4), and 25-OH-vitamin D. Results showed normal levels of Ca (82.1%), TSH (96.4%), and FT4 (96.4%), whilst 85.7% had vitamin D deficiency. DEXA results showed that within male athletes, juniors had a wider range of BMD than cadets, while within females, results did not vary, with no statistical difference between both males and females. Our results suggested that children and adolescents' BMD was positively related to TKD sport regardless of the abnormal weight loss strategies used, as evidenced by laboratory results. Children and adolescents should be conscious and practice TKD sport adopting healthy weight loss behaviors.